On becoming the hands and feet of Christ in an AIDS-ridden community in Swaziland – A story of hope - Wyngaard, A. van (Verbum et ecclesia, 2006)
In terms of the social involvement of the Christian church within the community, it would not be an overstatement to say that never before in history has there been a greater challenge facing the church than the present, finding a way to bring hope to those suffering due to the HIV/AIDS pandemic. Yet, in spite of the enormity of this pandemic, it is possible to make a huge difference in people’ s lives, making use of a few willing people and a fairly conservative budget. In this article the author attempts to describe the way in which a very small congregation, where the average weekly attendance at church services is seldom more than fifty people and where nearly all members live close to or under the breadline, started making a noticeable difference in their community. Motivated by God’ s love for them, they decided to share this love in a practical way with all those in the community suffering due to HIV/AIDS and other serious illnesses. This is a story of hope, not only for those who receive help, but even more so, for those who want to give help.